Safety and Efficacy of Tumor-Targeted Interleukin 12 Gene Therapy in Treated and Non-Treated, Metastatic Lesions - Cutrera, Jeffry; King, Glenn; Jones, Pamela; Kicenuik, Kristin; Gumpel, Elias; Xia, Xueqing; Li, Shulin (Current Gene Therapy, 2015)
The ability to control the immune system to actively attack tumor tissues will be a marvelous weapon to combat the persistent attack of cancer. Unfortunately, safe and effective methods to gain this control are not yet available as cancer therapies. To overcome the impediments to this control, tumor-targeted (tt) Interleukin 12 (IL-12) plasmid DNA can be safely delivered to accessible tumors, and these treatments can induce antitumor immune responses in both the treated and untreated tumors. Here, electroporationmediated ttIL-12 pDNA treatments are shown to be safe and well tolerated in a dose escalation study in canines bearing naturally-occurring neoplasms. The final patient in the dose-escalation study received up to 3,800 μg pDNA distributed among five separate squamous cell carcinoma tumors in doses equivalent to those administered in a Phase I trial with wildtype IL-12 pDNA. Not a single severe adverse event occurred in any patient at any of the five dose levels, and only minor, transient changes were noted in any tested parameter. Clinical response analysis and immune marker mRNA detection of treated and non-treated lesions suggest that ttIL-12 pDNA treatments in only a few tumors can elicit antitumor immune responses in the treated lesions as well as distant metastatic lesions. These observations and results demonstrate that ttIL-12 pDNA can be safely administered at clinical levels, and these treatments can affect both treated and nontreated, metastatic lesions.
Keywords: canine